2019
DOI: 10.1002/app.48737
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and flammability properties influenced by Zn/Al, Co/Al, and Ni/Al layered double hydroxide in low‐density polyethylene nanocomposites

Abstract: Layered double hydroxide (LDH) containing different metal constituents (Zn, Co, and Ni) was intercalated with different organic anions and has been used as fillers in low‐density polyethylene (LDPE), and its thermal and flammability behavior was evaluated. The best thermal stability (∆T0.5 = 21 °C) was obtained with the LDPE‐Ni/Al‐dodecyl sulfate (4 wt %) nanocomposite. Addition of hydrophobic LDHs systematically decreases the enthalpy of melting and crystallization compared to the neat polymer. In LDPE‐Co/Al‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…These results were consistent with those reported previously [37], indicating the successful NiAl-LDH fabrication. The interlayer spacing of the [003] plane was calculated according to Bragg equation [38] (d 003 = (l/(2sinu)) = 0.78 nm), which is consistent with Jaerger's report [33].…”
Section: Nial-ldh Characterisationsupporting
confidence: 83%
See 1 more Smart Citation
“…These results were consistent with those reported previously [37], indicating the successful NiAl-LDH fabrication. The interlayer spacing of the [003] plane was calculated according to Bragg equation [38] (d 003 = (l/(2sinu)) = 0.78 nm), which is consistent with Jaerger's report [33].…”
Section: Nial-ldh Characterisationsupporting
confidence: 83%
“…Jaerger et al fabricated three kinds of modified LDH for flame-retardant LDPE nanocomposite application. LDPE nanocomposites with 4 wt.% dodecyl sulphate modified nickel–aluminium layered double hydroxide (NiAl-LDH) addition possessed the best thermal stability as the initial degradation temperature increased by 21°C [33]. Karami et al prepared carbonate ( ) intercalated MgAl-LDH for fabricating flame-retardant epoxy resin (EP) nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Jaerper S. and his colleague compared three kinds of different metal constituents (Zn, Co and Ni) alkyl‐substituted LDHs for flame‐retardant low‐density polyethylene (LDPE). The results found that the flammability reduction for NiAl‐LDHs nanocomposites (2.0% fillers with 18% of reduction) was better than that of ZnAl‐LDHs (2.0% fillers with 10% of reduction) nanocomposites 13 . Zhou et al used polyphosphazene (PZS) modified NiCo‐LDHs to fabricate epoxy resin based nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…The results found that the flammability reduction for NiAl-LDHs nanocomposites (2.0% fillers with 18% of reduction) was better than that of ZnAl-LDHs (2.0% fillers with 10% of reduction) nanocomposites. 13 Zhou et al used polyphosphazene (PZS) modified NiCo-LDHs to fabricate epoxy resin based nanocomposites. The total heat release and peak heat release rate of the epoxy resin/modified NiCo-LDHs with 4 wt% loading decreased by 11.2% and 30.0%, respectively, which exhibited better smoke suppression performance.…”
Section: Introductionmentioning
confidence: 99%
“…At present, LDHs containing transition metals, such as CoAl-LDH, FeZn-LDH, CuAl-LDH, and CoNi-LDH, are also commonly used as flame retardants due to their special catalytic effects [ 11 , 37 , 38 , 39 , 40 ]. Jaerger et al [ 41 ]. intercalated CoAl-LDH, NiAl-LDH, and ZnAl-LDH with distinct organic anions as fillers for low-density polyethylene and evaluated their thermal stability and flammability.…”
Section: Introductionmentioning
confidence: 99%